Patient-Reported Body Image, Pain, and Satisfaction After Breast-Conserving Surgery, Mastectomy, and Mastectomy With Reconstruction: A Cross-Sectional Cohort Study - Noam Weiner; Eran Sharon; Tal Kind; Helit Nakar; Tomer Mimouni; Yehonatan Noyman; Lior Har-Shai; Assi Levi (Indian Journal of Surgical Oncology, 2026)
Abstract Background Surgical treatment for breast cancer may affect long-term body image, pain, and satisfaction, yet the relative contribution of surgical approach and patient-level factors remains uncertain. We evaluated patient-reported outcomes after breast-conserving surgery, mastectomy without reconstruction, and mastectomy with reconstruction. Methods In this cross-sectional cohort study, 230 women treated between 2015 and 2021 at a single Israeli tertiary center completed an investigator-developed Hebrew telephone questionnaire a mean of approximately 4 years after surgery. Composite and item-level outcomes for body image, pain intensity, pain-related quality of life, and satisfaction were analyzed using multivariable regression adjusted for demographic and clinical covariates. Results Breast-conserving surgery was associated with more favorable adjusted positive body-image, negative body-image, and satisfaction scores than both mastectomy groups (positive body image: 3.7 vs. 2.8 and 3.1, global P = 0.00053; negative body image: 2.1 vs. 3.1 and 2.9, global P < 0.001; satisfaction: 2.7 vs. 2.2 and 2.4, global P = 0.021 for breast-conserving surgery, mastectomy without reconstruction, and mastectomy with reconstruction, respectively). Adjusted pain intensity (2.3, 3.1, and 1.9; global P = 0.439) and pain-related quality-of-life scores (1.0, 1.9, and 1.6; global P = 0.275) did not differ significantly by surgical type. Higher BMI was associated with lower odds of favorable positive body image (OR, 0.91; 95% CI, 0.86–0.98; P = 0.008) and lower odds of less persistent pain (OR, 0.92; 95% CI, 0.87–0.98; P = 0.008). Each 10-year increase in age was associated with lower odds of reconstruction versus breast-conserving surgery (OR, 0.50; 95% CI, 0.31–0.81; P = 0.005) and versus mastectomy without reconstruction (OR, 0.27; 95% CI, 0.11–0.69; P = 0.010). Conclusion In this single-center cohort of Hebrew-speaking breast cancer survivors, surgical approach was associated with long-term body image and satisfaction, whereas pain outcomes were not clearly associated with surgical extent after adjustment. Because the study used an investigator-developed questionnaire in a culturally specific setting, the findings should be interpreted cautiously but support incorporation of patient-reported outcomes into shared decision-making for breast cancer surgery.